Estudio del Efecto de Campos Magnéticos en Citoesqueleto de Osteoblastos Humanos - Noriega-Luna, Berenice; Sabanero López, Myrna; Sosa Aquino, Modesto; Ávila-Rodríguez, Mario (Acta Universitaria, 2009)
In this work are presented the results obtained from the application of magnetic fields (MF), both pulsed (PMF) and static (SMF), on the morphology of human osteoblasts. The effectof such fields has been evaluated through the analysis of the structure of the Î²-tubuline, which is protein that forms part of the cellular cytoskeleton. The applied fields were 0.65 m Tand 0.5 mT for PMF and SMF, respectively. The application of the MF produces alterations in the pattern of normal distribution of microtubules, which gives rise to the formation of fluorescent aggregates in the cortical region of the cellular membrane. The obtained results with respect to the morphological changes in the osteoblasts clearly suggest that these are sensitive to stimulation with MFs, which alter its cellular activity through changes in cytoskeletal structures.
Keywords: Array; Array; Array; Array